Range of motion of body segments is larger during the maximal instep kick than during the submaximal kick in experienced football players - Langhout, R.; Tak, I.; van der Westen, R.; Lenssen, T. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Football players with groin injury refrain from maximal kicking. Previous groin injury is related to decreased hip range of motion (ROM). Information on ROM differences between maximal and submaximal kicking within players is lacking. The first aim of this study is to quantify ROM of body segments during the maximal (MaxK) and submaximal (SubK) instep kick at four key points. The second aim is to study ROM differences of tension arc and movement trajectories between MaxK and SubK.